The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15388/infedu.2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Game-Based Learning for Students with Intellectual Disabilities – A Systematic Literature Review

Abstract: The purpose of this systematic literature review is to explore the area of digital Game-Based Learning (GBL) for students with intellectual disabilities as a tool that enables positive impact on learning and mastering specific skills in order to make recommendations for future research. Twenty-one studies were selected from different databases. The results showed that the most common type of game was serious game, and the most common used technology was PC with additional equipment, but tablets were also often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…Pembelajaran yang menyenangkan memang sangat cocok untuk diterapkan dalam pembelajaran PPKn SD. Menggunakan konten e-learning berbasis motion graphic dan website wordpress dapat dikatakan hal yang menyenangkan bagi usia anak-anak sekolah dasar (Forgó, 2013;Önal & Alemdağ, 2018;Pati & Majhi, 2019;Stančin et al, 2020) Nama produk dibuat semudah mungkin untuk memudahkan peserta didik dan pendidik lebih cepat dan mudah dalam mengingatnya. Sesuai dengan pendapat Gunawan, bahwa formula dalam membuat merek adalah; mudah diingat, mengandung makna, familiar, unik, serta baru.…”
Section: Hasil Dan Pembahasanunclassified
“…For instance, Lämsä et al ( 2018 ) reviewed 20 studies that addressed learning disabilities by employing game-based technological applications to support learners' basic reading and math skills. Additionally, Stančin et al ( 2020 ) explored 21 studies related to the use of digital-assisted educational games for learners with intellectual disability. As these studies can only provide a partial picture of the use of game-based learning in the realm of special education, a comprehensive review of how to apply educational games to enhance the learning of individuals with diverse disability profiles is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this review is intended to fill this gap by including different disabilities (e.g., hearing impairment, autism spectrum disorder, and intellectual disability). Additionally, several literature reviews related to game-based learning and special education focused on the technology assessment perspective in terms of the adopted operating system and technology (Stančin et al, 2020 ). However, limited findings were presented in the literature about how learners with different disabilities might perceive game-based learning, stakeholders involved in the learning process and which elements should be considered when designing game-based learning for learners with disabilities.…”
Section: Introductionmentioning
confidence: 99%